Active and passive strategies for managing the economic security of economic entities in the conditions of traditional and innovative threats - O.V. Koval; D.V. Safonov (Економіка, управління та адміністрування)
The circumstances in which domestic subjects of economic activity try to function and achieve the goals of their existence are determined. In the conditions of traditional and new threats, there is a need to research approaches to strategic security-oriented management, which is designed to ensure continuous functioning and profitable operation of business structures, regardless of the influence of external and internal environmental challenges on this process. The purpose of the study is to establish the characteristics and formative features of active and passive strategies for managing the economic security of economic entities, to establish their suitability for use in war conditions and during the post-war recovery of Ukraine's economy. The methods of historical analysis, content analysis, synthesis, generalization and graphic visualization were used in the research process. As a result, it was possible to obtain a set of factors that determine the features of effective strategic management of the economic security of economic structures, such as: war and occupation, the spread of Industry 4.0 and 5.0 trends, the variability of state economic policy, convergence with EU countries, the global pandemic of COVID-19 and its consequences, BANI World as an external environment for the functioning of enterprises, institutions, and organizations. The characteristics of active and passive economic security management strategies at the micro level are identified, their distinguishing features are determined, and it is concluded that the most effective economic security management strategy for Ukrainian enterprises in the conditions of a full-scale war can be a strategy that combines individual characteristics of active and passive strategies – that is, a strategy of mixed type, which, among other things, will be characterized by adaptability, flexibility, integration with the general strategy and personnel policy of the business entity.